Effect of Reduction of Trace Minerals from Feed for Seven Days before Marketing the Broilers on their Performance - Kuwar, Vivek V.; Kadam, Avinash S.; Dhumal, Manik V.; Mote, Chandrashekhar S.; Tumlam, Uma M.; Barate, Abhijit K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The trial was conducted to study the effect of reducing trace minerals from the finisher diet for seven days before marketing the broilers on their performance. Day-old commercial broiler chicks were randomly distributed into four treatments, each having 60 birds. Each treatment was further subdivided into four replicates of 15 birds. All 4 groups (A-D) received a similar pre-starter diet for the first 7 days, starter diet for the second and third week, and finisher diet for the fourth and fifth week. The finisher diet was supplemented with a 0.05% trace minerals mixture. During sixth week, Group A continued with a finisher diet supplemented with 0.05% trace minerals, while group B, C and D finisher diets were supplemented with trace minerals @ 75% (0.0375%), 50% (0.025%), and 0%, respectively, as compared to group A diet. The performance parameters were recorded at the end of sixth week. The antibody titers against NDV were performed on the 42nd day. The economics of the production was also calculated at the end of the experiment. The results of the experiment indicated that reduction or removal of trace minerals in finisher diet seven days before the marketing of broilers does not have a significant influence on average BW, WG, FI, FCR, BY, GY, EVSY, R-to-C, thymus, spleen, gait score, footpad score, and mortality, but it had a significant adverse effect on % weight of bursa of Fabricius, NDV titer, and net profit per bird and per kg weight.